CH3NH3PbI3 Perovskite Sensitized Solar Cells Using a D-A Copolymer as Hole Transport Material. (1st January 2015) - Nagarjuna, P.; Narayanaswamy, K.; Swetha, T.; Rao, G. Hanumantha; Singh, Surya Prakash; Sharma, G.D.
Graphical abstract: Abstract: A conjugated D-A copolymer (P) having benzodithiophene donor and benzo[1, 2, 5]thiadiazole acceptor was employed as a p-type hole transporting material in solid state organic–inorganic hybrid solar cells and compared with the P3HT hole transporting material. In these device we have used organo-lead halide (CH3 NH3 PbI3 ) synthesized by us, as light harvester. The power conversion efficiency (PCE) of 6.64% is achieved for the solar cell with P which is higher than that for P3HT (4.24%). The increase in PCE is mainly due to the enhancement in FF and Voc and attributed to higher mobility of hole for conjugated copolymer than P3HT.